The coming of age of water channels for separation membranes: from biological to biomimetic to synthetic - Lim, Yu Jie (2022)
Water channels are one of the key pillars driving the development of next-generation desalination and water treatment membranes. Over the past two decades, the rise of nanotechnology has brought together an abundance of multifunctional nanochannels that are poised to reinvent separation membranes with performances exceeding those of state-of-the-art polymeric membranes within the water-energy nexus. Today, these water nanochannels can be broadly categorized into biological, biomimetic and synthetic, owing to their different natures, physicochemical properties and methods for membrane nanoarchitectonics. Furthermore, against the backdrop of different separation mechanisms, different types of nanochannel exhibit unique merits and limitations, which determine their usability and suitability for different membrane designs. Herein, this review outlines the progress of a comprehensive amount of nanochannels, which include aquaporins, pillar[5]arenes, I-quartets, different types of nanotubes and their porins, graphene-based materials, metal- and covalent-organic frameworks, porous organic cages, MoS2, and MXenes, offering a comparative glimpse into where their potential lies. First, we map out the background by looking into the evolution of nanochannels over the years, before discussing their latest developments by focusing on the key physicochemical and intrinsic transport properties of these channels from the chemistry standpoint. Next, we put into perspective the fabrication methods that can nanoarchitecture water channels into high-performance nanochannel-enabled membranes, focusing especially on the distinct differences of each type of nanochannel and how they can be leveraged to unlock the as-promised high water transport potential in current mainstream membrane designs. Lastly, we critically evaluate recent findings to provide a holistic qualitative assessment of the nanochannels with respect to the attributes that are most strongly valued in membrane engineering, before discussing upcoming challenges to share our perspectives with researchers for pathing future directions in this coming of age of water channels.